Clinical Profile and Diagnosis of Obstructive Sleep Apnea Syndrome using Overnight Polysomnography in a Tertiary Care Hospital - Pokharel, M.; Shrestha, B. L.; Dhakal, A.; Rajbhandari, P.; Shrestha, K. S.; KC, A. K.; Bhattarai, A.; Karki, D. R. (Kathmandu University Medical Journal, 2021)
Background Obstructive sleep apnea is a highly prevalent yet largely under-diagnosed disease that poses a significant burden on the healthcare system. Objective To determine the role of predictors for Obstructive sleep apnea syndrome and its severity in Nepalese population. Method Prospective and analytical study conducted in the Department of Otorhinolaryngology and Head and Neck surgery at Kathmandu University Hospital between March 2018 and June 2020. A total of 85 adult patients with Obstructive sleep apnea with an Epworth sleepiness score greater than 10 were included. Overnight polysomnography was done and scoring of sleep associated events were done according to the American Academy of Sleep Medicine criteria. Participants were classified as simple snoring and mild, moderate or severe Obstructive sleep apnea syndrome groups depending on the Apnea Hypopnea Index values. Relationship of Apnea hypopnea index was analyzed with age, neck circumference, body mass index and Epworth Sleepiness score. Result Simple snoring was seen in 18(21.17%) patients, 14(16.47%) had mild Obstructive sleep apnea, 13(15.29%) had moderate Obstructive sleep apnea, whereas the severe group consisted of 40(47.05%) patients. The minimum Epworth Sleepiness Score was 10 and the maximum was 25. The Apnea hypopnea index correlated positively with Body mass index (p=.010) and Epworth sleepiness score (p<.001). However, Apnea hypopnea index had no association with age (p=.437) and neck circumference (p=.118). Conclusion Health professionals need to be extremely vigilant while examining patients presenting with Obstructive Sleep Apnea. Polysomnography is the investigation of choice in the early identification of this treatable disease.